3D FEM analysis of flexible base asphalt pavement structure under non-uniform tyre contact pressure. Issue Volume 20:Issued 9(2019) (2nd September 2019) - Jiang, Xin; Zeng, Cheng; Gao, Xiaofeng; Liu, Zhujun; Qiu, Yanjun
Abstract: Circular uniform pressure distribution has been traditionally utilised in the analysis of mechanical-based asphalt pavement. However, both the magnitude along tyre width and length shows non-uniformity. Thus, EverStressFE, a 3D software package, was applied to establish a numerical model of the flexible base asphalt pavement structure under non-uniform vertical tyre contact pressure. Comparisons were made among the distribution of non-uniformity and uniformity on pavement surface deflection, pavement structure shear strain, the tensile strain at the bottom of the asphalt concrete surface layer and the vertical compressive strain on the top of the subgrade. The control index on the design life of the pavement under the non-uniform vertical contact pressure was discussed. The results show that, compared with uniform distribution, convex non-uniform distribution produces larger deflection on the pavement surface and maximum tensile strain at the bottom of the asphalt concrete surface layer, while the concave one generates larger shear strain on the pavement structure. Meanwhile, the non-uniform distribution has a little effect on the vertical compression strain on the subgrade top except for the convex half sine wave non-uniform distribution. And the maximum tensile strain at the bottom along the driving direction is larger than that along the tyre width regardless of the wheel loading distribution. In addition, the damage for the flexible base asphalt pavement structure is permanent deformation, specifically the allowable number of load repetitions to limit rutting for convex half sine wave non-uniform distribution is the smallest among all the computational cases.